THEORETICAL PERSPECTIVES ON THE PARTONYMIC (HOLO-MERONYMIC) PHENOMENON IN ENGLISH AND UZBEK LANGUAGES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article presents theoretical perspectives on when the concept of the partonymic (holo-meronymic) phenomenon first emerged in English and Uzbek linguistics, the stages of its development, and its introduction into the field of linguistics.